Sustainable plant-based protein hydrolysates: Utilization of waste proteins modified by enzymatic hydrolysis in techno-functional applications - Bekiroglu, Hatice; Acar, Zeynep Deniz; Sagdic, Osman (ELSEVIER, 2025)
The increasing global demand for sustainable and nutritious food options has accelerated the development of plant-based food ingredients. Plant proteins are gaining widespread recognition for their health benefits, sustainability, and lower environmental impact compared to animal-derived proteins. However, traditional plant protein sources such as legumes, cereals, and oilseeds are often limited by availability and resource constraints. Consequently, there is a growing focus on utilizing plant-based waste materials, such as agricultural residues and food processing by-products, as novel protein sources. Plant protein hydrolysates (PPHs), obtained through enzymatic hydrolysis, have attracted significant attention due to their enhanced functional properties, including improved solubility, emulsification, foaming, and gelation. These properties are crucial for their application in food formulations, including meat substitutes, dairy alternatives, and nutraceuticals. Additionally, the enzymatic hydrolysis enhances the bioactive potential of proteins, offering antioxidant, anti-inflammatory, and antimicrobial benefits. This review explores the techno-functional characteristics of plant protein hydrolysates derived from agricultural waste and their potential applications in the food industry. By repurposing plant-based waste, this approach addresses the increasing demand for plant-based ingredients while promoting sustainability and waste reduction within the food sector, as well as in the pharmaceutical and cosmetics industries.
Keywords: Enzymatic hydrolysis; Emulsion activity-stability; Foaming; Solubility; Gelation; SOY PROTEIN; EMULSIFYING PROPERTIES; ANTIOXIDANT ACTIVITIES; FOAMING PROPERTIES; PEA PROTEIN; EXTRACTION; PEPTIDES; POLYSACCHARIDES; OPTIMIZATION; IMPROVEMENT; Biochemistry & Molecular Biology; Chemistry; Polymer Science